Exclusive breastfeeding and reduced risk of type 1 diabetes mellitus in children - Hsieh, Peter Prayogo; I Gusti Ayu Putu , Eka Pratiwi; I Made, Arimbawa; I Gusti, Lanang Sidiartha; Sindhughosa, Wega Upendra; I Made, Darma Yuda (Indonesian Pediatric Society, 2026)
Background There was a 7-fold increase in the prevalence of type 1 diabetes mellitus (T1DM) in Indonesia from 3.88/100,000,000 in 2000 to 28.19/100,000,000 in 2010. Previous studies have shown small reductions in the risk of developing T1DM associated with exclusive breastfeeding. This topic has not been well explored in Indonesian children with T1DM. Objective To assess for a possible association between T1DM and exclusively breastfeeding. Methods This matched, case-control study included children who visited clinics or were hospitalized from January-March 2025 (case group). The control group comprised children from a Catholic private school. The inclusion criteria for the case group were children aged >24 months to <18 years who had been diagnosed with TIDM by a doctor and had complete electronic medical records (EMR). The exclusion criterion was incomplete EMR. The inclusion criteria for the control group were children without T1DM who were aged >24 months to <18 years. Subjects’ characteristics and history of breastfeeding were obtained from the interview and questionnaire. The association between T1DM and exclusively breastfeeding were analyzed using McNemar analysis and logistic regression was done for confounding factors. Results Of the 42 subjects in each group, 27 (64.3%) subjects with T1DM and 16 (38.1%) subjects in the control group were not exclusively breastfed. McNemar analysis revealed a significant association between not exclusively breastfeeding and greater risk of T1DM (OR=3.99; 95%CI 1.44 to 11.04; P=0.008). Conclusion There is a significant association between exclusive breastfeeding and T1DM. Those who were not exclusively breastfed are 3.99 times more likely to develop T1DM.